Characteristics of immune response in patients with acute chronic maxillary sinusitis associated with intra-cellular bacterial infections - O. V. Parilova (Sankt-Peterburg : NIIÈM imeni Pastera, 2020)
Currently, chronic inflammatory pathology of paranasal sinuses mostly affecting maxillary antrum is one of the pressing issues for health care. Over the last two decades, a great etiological importance in inducing inflammation in paranasal sinuses was referred to bacterial intracellular infections caused by Mycoplasma and Chlamydia. In particular, Chlamydia, whose life cycle is closely linked to residence inside host cells defines them as pathogenic obligate intracellular gram-negative bacteria, whereas Mycoplasma is a membrane-associated microorganism able to self-replication and long persistence on host cellular membranes. Increased incidence of chronic pathology in paranasal sinuses associated with intracellular infection is shaped by a range of circumstances, primarily increased prevalence of immunocompromised subjects, worsened social and ecological conditions, uncontrolled and unjustified administration of available of antimicrobials and anti-septic agents, hormone preparations altering community of extracellular microbe populations (microbiocenoses), inhabiting natural biotope in the upper respiratory tract mucosa. These factors contribute to the lowering colony resistance, entrance and propagation of Chlamydia and Mycoplasma as a monoor mixed infection. Upon that, mixed variants of Chlamydia-Mycoplasma infection are characterized by development of more severe sinusitis accompanied with diverse complications in the lower respiratory tract, digestive tract, urinary and nerve system. There were examined 189 subjects for assessing epidemiologic characteristics and features of systemic and mucosal immune responses in patients with exacerbated chronic maxillary sinusitis associated with intracellular bacterial infection. Presence of intracellular bacterial infection was confirmed by laboratory tests: direct immune fluorescent analysis and PCR. It was found that high prevalence of Сhlamydia trachomatis, Chlamydophila pneumoniae and Mycoplasma pneumoniae in patients with exacerbated chronic inflammatory pathology of paranasal sinuses. Comparing laboratory test data for patients with identified intracellular bacterial pathogens vs. those with negative results revealed a common trend in pathologic immune-related changes that fits to typical host anti-infection response manifested by inflammatory process. Besides, we described features of immune reactivity in patients with verified Chlamydia infection including more pronounced unbalance in Т cell immunity as well as evelated parameters of humoral immunity in patients with verified Chlamydia and Mycoplasma infection.